Comment on "From Plant Traits to Plant Communities: A Statistical Mechanistic Approach to Biodiversity" - Marks, Christian O.; Muller-Landau, Helene C. (Science (American Association for the Advancement of Science), 2007)
Shipley et al . (Reports, 3 November 2006, p. 812) predicted plant community composition and relative abundances with a high level of accuracy by maximizing Shannon's index of information entropy (species diversity), subject to constraints on plant trait averages. We show that the entropy maximization assumption is relatively unimportant and that the high accuracy is due largely to a statistical effect.